2017
DOI: 10.4103/ijpvm.ijpvm_124_17
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of two extracts of Cydonia oblonga miller (Quince) fruits on gastric ulcer induced by indomethacin in rats

Abstract: Background:In various studies, Cydonia oblonga Miller (quince) has been reported to have many properties such as antioxidant and anti-ulcerative effects. This study has aimed to investigate the protective effects of quince aqueous extract (QAE) and quince hydroalcoholic extract (QHE) on gastric ulcer caused by indomethacin and the relevant macroscopic, histopathology, and biochemical factors in rats.Methods:Ten groups of male Wistar rats, six in each, were used in this study. These groups included: normal (dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…Standard pepsin was used to draw the standard curve for pepsin activity while, 10 min later, 5 mL of trichloroacetic acid was added to terminate the reaction. After filtration, optical absorbance of amino acids produced by the reaction of pepsin with hemoglobin was measured at the wavelength of 280 nm, and pepsin activity was determined in terms of mg after 15 min ( 30 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Standard pepsin was used to draw the standard curve for pepsin activity while, 10 min later, 5 mL of trichloroacetic acid was added to terminate the reaction. After filtration, optical absorbance of amino acids produced by the reaction of pepsin with hemoglobin was measured at the wavelength of 280 nm, and pepsin activity was determined in terms of mg after 15 min ( 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…The stomach was then cut into two longitudinal sections for further examination. One section was placed into formalin solution (10%) and sent for pathological examination to assess inflammation severity, hemorrhagic spot, sub-mucosal edema, and superficial mucosal ulcers ( 30 ). The other section was used for the measurement of myeloperoxidase (MPO) activity and malondialdehyde (MDA) value.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[65] This could possibly be attributed to diverse compositions, which are responsible for the synergistic effects of natural products with PSO not an exception. Recently, some authors have suggested the possible mechanisms of the active compounds in PSO [61,62,[66][67][68] based on the physiological effect studied ( Figure 2). Lately, PSO was shown to promote peak bone mass via increased insulin-like growth factor type 1 (IGF-1) expression in liver as well as signaling in bone.…”
Section: Biological Properties and Possible Mechanisms Of Psomentioning
confidence: 99%
“…Dentro de sus usos medicinales, encontramos que tradicionalmente diferentes partes de las plantas tales como raíces, frutas, hojas y semillas se utilizan para el tratamiento de varias enfermedades, entre ellas: diarrea, tos, disentería, dolor de garganta, estreñimiento y bronquitis 9,10 . Además, de forma industrial, su fruto es usado como protector mucoso en el Síndrome de intestino irritable y úlcera péptica 11,12 .…”
Section: Pág 20unclassified